Effect of the Phospholipid Chain Length and Head Group on Beta‐Phase Formation of Poly(9, 9‐dioctylfluorene) Enclosed in Liposomes. (7th September 2013) - Tapia, María J.; Monteserín, María; Burrows, Hugh D.; Seixas de Melo, João S.; Estelrich, Joan
Abstract : We have studied the effect of head group and alkyl chain length on β ‐phase formation in poly(9, 9‐dioctylfluorene) (PFO) solubilized in phospholipid liposomes. Systems studied have three different alkyl chain lengths (1, 2‐dimyristoyl‐ sn ‐glycero‐3‐phosphatidylcholine [DMPC], 1, 2‐didodecanoyl‐s n‐ glycero‐3‐phosphatidylcholine [DLPC], 1, 2‐dipalmitoyl‐ sn ‐glycero‐3‐phosphatidylcholine [DPPC]) and head groups (1, 2‐dimyristoyl‐ sn ‐glycero‐3‐phosphate monosodium salt [DMPA], 1, 2‐dimyristoyl‐ sn ‐glycero‐3‐phosphoethanolamine [DMPE] and 1, 2‐dimyristoyl‐ sn ‐glycero‐3‐phospho‐l ‐serine sodium salt [DMPS]). Changes in liposome size upon addition of PFO are followed by dynamic light scattering. All the phospholipids induce the formation of PFO β ‐phase, which is followed by the emission intensity and deconvolution of the absorption spectra. Both the head group and alkyl chain length affect the yield of β ‐phase. The photophysics of PFO incorporated in liposomes is characterized by stationary and time‐resolved fluorescence, whereas the polymer‐phospholipid interactions have been studied by the effect of the PFO concentration on the phospholipid phase transitions (differential scanning calorimetry [DSC]). Abstract : Poly(9, 9‐dioctylfluorene) is solubilized in phospholipid liposomes of DLPC, DMPC, DPPC, DMPE, DMPA, and DMPS giving rise to the formation of the ordered polymer β ‐phase which is characterized by a well‐resolved characteristic vibronic structure in the emission spectra, higher luminescence efficiency and improved charge transport properties resulting from increased electron delocalization. This phase is better promoted by phospholipids with longer alkyl chain lengths or non‐bulky and more hydrophobic head groups. The polymer agglomeration is considered the main mechanism for β ‐phase formation in these systems. A second driving force seems to be the interdigitation between the polymer and phospholipid alkyl chains.